PENGARUH MOTIVASI INTRINSIK DAN EKSTRINSIK TERHADAP KINERJA PENGEMUDI GRABBIKE - Hamdani Hamdani; Rita Yuni Mulyanti; Fatimah Abdillah (STIE Muhammadiyah Jakarta, 2020)
This study aims to analyze the empirical evidence of the influence of intrinsic and extrinsic motivation on the performance of grabbike drivers operating in Bogor cities and districts. The population in this study were all Grabbike City and Bogor Regency drivers. Sampling is done by non probability sampling technique. Data were collected using a questionnaire and analyzed by multiple linear regression. The results showed that intrinsic motivation had a positive and significant effect on the performance of grabbike drivers in the city of Bogor. Extrinsic motivation influences the positive and significant performance of grabbike driver performance in the city of Bogor. The results also showed that the better intrinsic and extrinsic motivation of driver performance would increase.